Development and Validation of a Novel Prognostic Model for Acute Myeloid Leukemia Based on Immune-Related Genes - Li, Ran; Ding, Zuoyou; Jin, Peng; Wu, Shishuang; Jiang, Ge; Xiang, Rufang; Wang, Wenfang; Jin, Zhen; Li, Xiaoyang; Xue, Kai; Wu, Xiaolu; Li, Junmin (Frontiers in Immunology, 2021)
The prognosis of acute myeloid leukemia (AML) is closely related to immune response changes. Further exploration of the pathobiology of AML focusing on immune-related genes would contribute to the development of more advanced evaluation and treatment strategies. In this study, we established a novel immune-17 signature based on transcriptome data from The Cancer Genome Atlas (TCGA) and The Genotype-Tissue Expression (GTEx) databases. We found that immune biology processes and transcriptional dysregulations are critical factors in the development of AML through enrichment analyses. We also formulated a prognostic model to predict the overall survival of AML patients by using LASSO (Least Absolute Shrinkage and Selection Operator) regression analysis. Furthermore, we incorporated the immune-17 signature to improve the prognostic accuracy of the ELN2017 risk stratification system. We concluded that the immune-17 signature represents a novel useful model for evaluating AML survival outcomes and may be implemented to optimize treatment selection in the next future.